2007
DOI: 10.1177/1075547007308599
|View full text |Cite
|
Sign up to set email alerts
|

Can a Personality Trait Predict Talk About Science?

Abstract: Sensation seeking, a trait that has been invoked by public health campaign scholars as a targeting variable, also holds promise for informal science education professionals who seek to engage social networks in their promotion efforts. The authors contend that sensation seeking should positively predict talk about science, even after controlling for often-cited predictors such as education, relevant employment, perceived understanding of science, perceived relevance of science, and attitude toward science. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Specifically, there was a tendency for users and intenders to share in a direction that supported their current behavior or intentions. These results are in line with findings from previous studies that show people are generally more likely to talk about personally relevant issues (Hwang & Southwell, 2007) and show they also hold true in the context of tobacco and e-cigarette communication. Furthermore, relevance predicted sharing in the long run, but only for e-cigarettes: given that more than two-thirds of e-cigarette sharers tended to share either positive or a mix of positive and negative content, and considering that e-cigarettes are relatively novel products, it may be that current e-cigarette users and intenders are regularly sharing e-cigarette-related content in order to gain some validation of their vaping behavior or intentions, or to obtain more information about the benefits and/or consequences of vaping.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, there was a tendency for users and intenders to share in a direction that supported their current behavior or intentions. These results are in line with findings from previous studies that show people are generally more likely to talk about personally relevant issues (Hwang & Southwell, 2007) and show they also hold true in the context of tobacco and e-cigarette communication. Furthermore, relevance predicted sharing in the long run, but only for e-cigarettes: given that more than two-thirds of e-cigarette sharers tended to share either positive or a mix of positive and negative content, and considering that e-cigarettes are relatively novel products, it may be that current e-cigarette users and intenders are regularly sharing e-cigarette-related content in order to gain some validation of their vaping behavior or intentions, or to obtain more information about the benefits and/or consequences of vaping.…”
Section: Discussionsupporting
confidence: 92%
“…The second class of predictors was perceived topical relevance. Research has consistently shown that people are likely to invest more effort into talking about information that they deem relevant to themselves (Hwang & Southwell, 2007; Southwell, 2013). People tend to talk about identity-relevant topics, either as a way to manage and maintain one’s impression (Berger, 2014) or simply because personally relevant topics are most frequently thought about and therefore, most salient (Leippe & Elkin, 1987; Southwell, 2005).…”
Section: The Current Studymentioning
confidence: 99%
“…Prior work finds that individual differences (e.g., demographic characteristics) can influence the likelihood of engaging in certain types of conversations (e.g., about science) [32]. As many households include occupants of different genders, it is necessary to consider the potential role of gender in household interactions around thermal comfort.…”
Section: Variation In Thermal Comfort Preferences Across Occupantsmentioning
confidence: 99%
“…Finally, personality psychologists have recognised that people vary in sensation‐seeking, ‘a trait defined by the seeking of varied, novel, complex, and intense sensations and experiences, and the willingness to take physical, social, legal, and financial risks for the sake of such experiences’ (Zuckerman, 1994 , p. 27). This trait implies that some people find anxiety‐provoking and uncertain situations rewarding, which pertains not only to genuinely risky behaviours (e.g., extreme sports; gambling) but also to risk‐free activities that bring excitement, novelty, and intense emotions such as attending scary movies, playing chess, and talking about science (Hwang & Southwell, 2007 ; Joireman, Fick, & Anderson, 2002 ; Morris & Griffiths, 2013 ; Roberti, 2004 ; Zuckerman, 1994 ).…”
Section: Introductionmentioning
confidence: 99%